2014
DOI: 10.14238/pi54.6.2014.372-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, high-dose corticosteroids, and renal infiltration in children with acute lymphoblastic leukemia

Abstract: Background Hypertension is a rarely recognized complicationof acute lymphoblastic leukemia (ALL). The incidence ofhypertension in ALL patients in Indonesia remains unknown,but the most common risk factors are corticosteroid use duringinduction-phase chemotherapy and renal leukemic infiltration.Objective To determine the incidence of hypertension in childrenwith ALL, and to assess for associations of high-dose corticosteroids,renal infiltration, and hyperleukocytosis to hypertension.Methods This was a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…A study involving acute lymphoblastic leukemia (ALL) children reported that the risk factors for HT include high dose corticosteroids, hyperleukocytosis, tumor lysis syndrome, kidney leukemic infiltration, and sepsis. [21,22] This cross-sectional study showed that 14% of patients with ALL had HT. [23] Other studies reported a higher incidence of HT among children with ALL or lymphoma.…”
Section: Discussionmentioning
confidence: 95%
“…A study involving acute lymphoblastic leukemia (ALL) children reported that the risk factors for HT include high dose corticosteroids, hyperleukocytosis, tumor lysis syndrome, kidney leukemic infiltration, and sepsis. [21,22] This cross-sectional study showed that 14% of patients with ALL had HT. [23] Other studies reported a higher incidence of HT among children with ALL or lymphoma.…”
Section: Discussionmentioning
confidence: 95%
“…Glucocorticoids form the backbone of induction and reinduction phases of ALL therapy and hypertension is an important though often under-reported non-hematological toxicity associated with its use. [8][9][10][11][12][13] No study has been conducted on pediatric population in Bangladesh. Through the study, we shall come to know about the incidence and risk factors of hypertension in childhood acute lymphoblastic leukemia which would give more insight into the spectrum of problem and would help to design follow-up plans and in planning treatment in our population.…”
Section: Introductionmentioning
confidence: 99%